RHUPUS Syndrome in Children: A Case Series and Literature Review - Vahid Ziaee; Mohammad Hassan Moradinejad; Reyhaneh Bayat (Case Reports in Rheumatology)
Objective. Overlap of juvenile idiopathic arthritis (JIA) and juvenile systemic lupus erythematosus (JSLE) is a rare clinical condition in children. This condition has been described as RHUPUS syndrome. Prevalence of this syndrome and 3 cases are reported in this paper. Cases Presentation. During 10 years, 3 patients with SLE had chronic arthritis before or after diagnosis of SLE. Prevalence of this disorder in JSLE was 2.5%. Two patients were females and one of them was a male. According to our review, mean delay between chronic joint involvement and JSLE diagnosis was 50.1 months. In our case report, two females had joint erosion and one of them died due to heart failure, but in the literature review, just 45% cases had joint erosion and 70% cases were polyarticulare form. Conclusion. RHUPUS is unusual presentation of lupus in children. It seems that clinical feature and outcome of RHUPUS syndrome are different in children due to difference between RA and JIA. We suggest juvenile RHUPUS for overlap of JIA and JSLE.